La notion de ‘awra selon Abû l-Ḥasan ‘Alî b. Muḥammad b. al-Qaṭṭân al-Fâsî (m. 628 /1231) - Eric Chaumont (Revue des Mondes Musulmans et de la Méditerranée)
Ibn al-Qaṭṭân al-Fâsî (d. 628/1231) was a scholar in the service of the Almohad regime (524-667/1130-1269). He is the author of probably the most exhaustive treatise ever written in Islam on the body as it could be “shown” or “looked at” according to the divine Law. This treatise analyses a topic which is constituent to the Alomohad ideology : the reassessment of the legal prescritions related to the body as it arouses passions among human beings, especially men, but also women. The elaborate analysis of Ibn al-Qaṭṭân evolves around the Coranic concept of ‘awra. His list of what is ethically and legally forbidden does not rely on the idea of the body as sacred, but rather seeks to protect the purity of lineages, believed to be a reflection of the created “nature.” The puritanism of Ibn al-Qaṭṭân which comes out in his Kitab al-Naẓar affects mainly women, and reminds us of some contemporary Islamic movements.